The Impact of Work Family Conflict, Workload and Transformational Leadership 0n Job Satisfaction and Employee Labour Loyalty of Nurses at Hospital XYZ Lampung - Nabila, Alma Rizkita (Jurnal Ilmiah Sumber Daya Manusia, 2024)
This study was conducted to examine and analyse the effect of Work Family Conflict, Workload and Transformational leadership on Job Satisfaction and Loyalty in nurses of XYZ Lampung Hospital. The method in this research is quantitative research with Hypothesis test. Respondent data was taken by purposive sampling with a questionnaire using a Likert scale (1-5). The object of research is all nurses of XYZ Lampung Hospital. The total sample was 160 people with the criteria of nurses with active status and at least 1 year of work. Data were analysed with the Partial Least Square Structural Equation Model (PLS-SEM) approach. The results showed that Work Family Conflict was proven to have a negative and significant effect on Job Satisfaction. Workload is proven to have a negative and significant effect on Job Satisfaction. Transformational leadership is proven an effect positive and significant to Job Satisfaction. Job Satisfaction has a positive and significant effect on Employee Loyalty. Management needs to overcome Work Family Conflict, workload, and encourage transformational leadership to increase Job Satisfaction and Employee Loyalty. Flexibility, resource planning, and leadership training need to be the main focus. These conclusions support productivity and organisational sustainability. There are a number of limitations followed by suggestions for future research.